Moral judgment and interpersonal values in students of high school of cities from Lima and Jauja - Matalinares Calvet, María (2009)
This research had like a purpose to establish a relation between the Moral Judgment and the Interpersonal Values of the students of 4th. and 5th. of High School, from male and female, whose ages were of 14 to 18 years old, coming from various state’s educative institutions, from Lima and Jauja, they answered a Development of Sociomoral Reflection Test by Kohlberg, adapted by Majluf (1986) and the Survey of Interpersonal Values (SIV) by Leonard Gordon, adapted by Higueras (1972) and Perez (1987). The results were processed by the squared Chi, and it was founded that Moral Judgment and Interpersonal Values are correlated. The Moral Judgment is related to the dimensions of Conformity, Recognition and Benevolence. Besides, data were processed with the U of Mann-Whitney Test showing highly significant differences between the students of Jauja and Lima at interpersonal values test; however, with the moral judgment it does not happen the same, since the students from Jauja and Lima they respond of similar form. In dimensions of Conformity, Recognition and Benevolence, there were differences in relation to the sex, being women who obtained better results than men, not happened the same in the case of the Moral Judgment. Finally, there were significant differences between Moral Judgment and Interpersonal Values based on the instruction level.